Prevention of debonding failure of intermediate anchor to eliminate premature shear failure of flexurally strengthened reinforced concrete beams - Alam, M.A.; Jumaat, Mohd Zamin (2015)
This research proposed an optimal method of intermediate anchor to prevent premature debonding failure of anchor plate for eliminating premature shear failure of CFRP laminate flexurally strengthened reinforced concrete (RC) beam. In the experimental programme, seven RC beam specimens were prepared which included un-strengthened control beam and flexurally strengthened beams with CFRP laminate. The flexurally strengthened beams were further shear strengthened using L-shaped intermediate anchors based on proposed and conventional methods. The experimental results of specimens were compared with the numerical results. Theoretical model had also been proposed to predict the debonding failure of intermediate anchors. Results showed that the anchors obtained based on the proposed design guideline prevented premature debonding failure of anchor plates completely and thus, the proposed intermediate anchored strengthened beams did not show premature shear failures. Whereas beams having the anchor plates based on conventional method failed by premature debonding of anchor plates followed by premature shear. The proposed intermediate anchors significantly increased the ultimate loads and ductility of the beams as compared to conventional one. It also reduced the number and widths of cracks in shear span. The theoretical model could predict the debonding failure load of intermediate anchor which was comparable with the experimental finding. Finally, numerical model predicted the structural behaviour of proposed intermediate anchored strengthened beams satisfactorily.